Atomic resolution imaging of graphene by transmission electron microscopy. - Robertson, A; Warner, J (2013)
The atomic structure of a material influences its electronic, chemical, magnetic and mechanical properties. Characterising carbon nanomaterials, such as fullerenes, nanotubes and graphene, at the atomic level is challenging due to their chemical reactivity and low atomic mass. Transmission electron microscopy and scanning probe microscopy are two of the leading methods for imaging graphene at the atomic level. Here, we report on recent advances in atomic resolution imaging of graphene using aberration-corrected high resolution transmission electron microscopy and how it has revealed many of the structural deviations from the pristine monolayer form. Structures in graphene such as vacancy defects, edges, grain boundaries, linear chains, impurity dopants, layer number, layer stacking and bond rotations are explored.